Three essays in the corporate use of financial derivatives - Tran, Long Phi (2020)
This thesis discusses three topics concerned with the corporate use of financial derivatives. The first paper studies the effects of interest rate swaps on firms’ default risk. The second paper examines the relationship between creditor rights and airlines’ hedging behaviour. The final paper investigates how managerial holdings of inside debt (pension benefits and deferred compensation) can impact the decision to hedge via the use of interest rate swaps. The first paper attempts to examine the question of whether the use of interest rate swaps by corporates and the direction of interest rate swaps increase or decrease firms’ probability of default. Our sample consists of United Kingdom (UK) listed non-financial firms for the period between 2001 and 2015. Using a pooled Ordinary Least Squares (OLS) model, we document that the use of interest rate swaps reduces the probability of default for both firms swapping into fixed and those swapping into floating. This result is robust when we use a range of econometric methods, including a fixed effects model, a propensity score matching technique, an instrumental variables approach, and a System Generalised Method of Moments model. Additionally, we find that a failure to account for differences between small and large firms can lead to incomplete or misleading inferences of the impact of interest rate swap usage on firms’ default risk. Our results show that whereas the use of interest rate swaps by small firms, irrespective of the direction of the swap, leads to a reduction in their default risk, large firms that swap into floating-rate debt are associated with an increase in their probability of default. Additionally, we show that the negative impact of swapping into fixed rate debt on firms’ default risk remains the same during the period of heightened economic policy uncertainty, whereas the effectiveness of swapping into floating rate debt in decreasing firms’ probability of default is weakened during this period. Moreover, this paper demonstrates that the recent period of zero lower bound interest rates affects the efficacy of swapping into fixed rate debt versus swapping into floating rate debt. Our results indicate that while swapping into fixed rate debt leads to a reduction in the probability of default during the zero lower bound period, the risk-mitigating effects of swapping into floating rate debt are significantly dampened during this period. In the second paper, we use a sample consisting of airlines from 36 countries over the period from 2002 to 2016 to investigate the impact of creditor rights on corporate hedging behaviour, measured by the extent of jet fuel hedging. Using a pooled Ordinary Least Squares model, we find that airlines undertake more jet fuel hedging in stronger creditor rights countries. These results are robust when we employ other econometric methods, such as a Tobit model, a Heckman model, or an instrumental variable technique. Moreover, we identify six creditor rights reforms during our sample period and employ a model that is akin to a difference-in-difference model. The results show that the change that increases the creditor rights index can lead to an increase in airlines’ jet fuel hedging. In addition, we find that the positive impact of creditor rights on the extent of jet fuel hedging is weakened during the financial crisis but strengthened during periods of high jet fuel prices. This study also sheds new light on the role of hedging in ameliorating the adverse effects of strong creditor rights. We show that jet fuel hedging can boost an airline’s leverage. Furthermore, hedging allows an airline to engage in high-risk but potentially value-enhancing investment activities, therefore alleviating the underinvestment problem observed in strong creditor rights countries. The third paper looks at how managerial compensation incentives, measured using data on the chief executive officer (CEO) pension benefits and deferred compensation (commonly referred to as inside debt), affect the decision to hedge via the use of interest rate swaps. Our sample consists of 912 listed United States (US) firms during the periods from 2006 to 2014. Using a probit model, we show that firms with more CEO inside debt are less likely to use interest rate swaps. Moreover, using a pooled OLS model, we find a negative relationship between CEO inside debt holdings and the extent to which a firm hedges using interest rate swaps. In this paper, we attempt to distinguish between protected and non-protected CEO inside debt. Whereas protected CEO inside debt is funded and secured, the non-protected one is not. Our result suggests that the negative association between CEO inside debt and hedging by interest rate swaps only exists if the CEO inside debt is non-protected. These results are robust when we employ a range of different econometric methods, including a Tobit regression model and an instrumental variables technique. Furthermore, we show that the negative impact of non-protected CEO inside debt is weakened when firms are financially constrained or during periods of heightened interest rate uncertainty. Finally, we document that non-protected CEO inside debt can have negative effects on firms’ default risk. However, our further analysis indicates that the negative effects of non-protected CEO inside debt on firms’ default risk are dampened when firms hedge using interest rate swaps, which can explain why firms with large CEO inside debt holdings hedge less with interest rate swaps.